POLA PENANGANAN GENANGAN AIR HUJAN DENGAN PENDEKATAN KONSEP BLUE GREEN CITIES DI KAWASAN KAMPUS UGM - Moh. Dahri Lumuan; Joko Sujono; Intan Supraba (Jurusan Teknik Sipil, Fakultas Teknik Sipil dan Perencanaan, Universitas Islam Indonesia, 2017)
Land use changes due to the expansion of the construction of educational infrastructure facilities at the Gadjah Mada University (UGM) Campus Area continue to develop. As a result, the open space is decreasing. This condition causes the ability of the land to absorbing rainwater decreases so that runoff of surface water increases, and cause inundation. This is evidenced by the presence of puddles at 15 points monitoring during rain events. The purpose of this study is to reduce rainwater nundation by absorbing water into the ground based on the Blue Green Cities (BGC)concept. The method used is the green infrastructure method by building a absorbingpark/bearing park and roof garden. From the potential for the construction of absorbing park/bearing park covering an area of 517,740 m², only 9,006 m2 have bearing. While the potential of the roof garden is as large as 9,881 m², has not been used optimally. There is only one existing building has a garden roof, namely the Sanitary Engineering Laboratory in Kuningan. The calculation result of the capacity of the catchment garden in the rainy season period September 2016 to March 2017, the volume of rainwater that overflows was 8.14%. It is highly recommended that all existing parks be modified to be a garden with a beard, besides to maintain a green area can also reduce inundation points.